Towards real-time middleware for applications of vehicular ad hoc networks. - MEIER, RENE; CAHILL, VINNY (Springer-Verlag, 2005)
Applications of inter-vehicle and vehicle-to-roadside communication that make use of vehicular ad hoc networks (VANETs) will often require reliable communication that provides guaranteed real-time message propagation. This paper describes an event-based middleware, called RT-STEAM. Unlike other event systems, RT-STEAM does not rely on a centralized event broker or look-up service while still supporting event channels providing hard real-time event delivery. RT-STEAM event filtering can be based on subject, content and/or proximity. To guarantee real-time communication, we exploit proximitybased event propagation to guarantee real-time constraints within the defined proximities only. The proximity within which realtime guarantees are available is adapted to maintain time bounds while allowing changes to membership and topology, typical of VANETs. This Space-Elastic Model of real-time communication is the first to directly address adaptation in the space domain to guarantee real-time constraints.
Lecture Notes in Computer Science
Distributed Applications and Interoperable Systems: 5th IFIP WG 6.1 International Conference
PUBLISHED
(DAIS 2005)
Keywords: Keywords